Relationship between value-based behaviors among university students in Malaysia - Hairol Anuar Mak Din,; Nor Azlili Hassan,; Mansor Mohd Noor,; Ahmad Fakhrurrazi Mohammed Zabidi, (Penerbit Universiti Kebangsaan Malaysia, 2021)
The value-based behavior about the topic of this study has a relationship with values because the values are acting according to the choices based on the core values of a society. The government’s efforts in achieving the idea of social cohesion and unity in Malaysian society are not confined to the policies and rules of authority alone, but also include the responsibility of the society at the grassroots level to engage in various daily activities across the ethnic and religious boundaries. Thus, this paper measures value-based behavior among university students through a value-based approach. This quantitative study targets university students from 10 public universities and two private universities in Malaysia. A total of 514 respondents consisting of university students of various ethnicities and religions. The findings are based on the value determination scale which is divided into two dimensions, namely positive value and negative value. There are three indicators for the positive values, namely; 1. The dimension of Doing Good Deeds (Al-Bir), 2) Dimension of Improvement (Al-Islah) and 3) Dimension of Justice (Al-Qist). While the indicators for negative values can be divided into two namely; 1) Dimensions of Damage (Al-Fasad) and 2) Dimensions of Tyranny or Oppression (Al-Zulm). The results found that each item in each positive value and the value-based behavior is significantly shared among the university students regardless of their ethnicity. The students can effortlessly develop the good human behavior that leads to the production of intellectual individuals with decently standing and spiritually comprehensive in the society.